A bitter anti-inflammatory drug binds at two distinct sites of a human bitter taste GPCR - Peri, Lior; Matzov, Donna; Huxley, Dominic R.; Rainish, Alon; Fierro, Fabrizio; Sapir, Liel; Pfeiffer, Tara; Waterloo, Lukas; Hübner, Harald; Peleg, Yoav; Gmeiner, Peter; McCormick, Peter J.; et al. (Nature Communications, 2024)
Bitter taste receptors (TAS2Rs), a subfamily of G-protein coupled receptors (GPCRs) expressed orally and extraorally, elicit signaling in response to a large set of tastants. Among 25 functional TAS2Rs encoded in the human genome, TAS2R14 is the most promiscuous, and responds to hundreds of chemically diverse ligands. Here we present the cryo–electron microscopy (cryo-EM) structure of the human TAS2R14 in complex with its signaling partner gustducin, and bound to flufenamic acid (FFA), a clinically approved nonsteroidal anti-inflammatory drug. The structure reveals an unusual binding mode, where two copies of FFA are bound at distinct pockets: one at the canonical receptor site within the trans-membrane bundle, and the other in the intracellular facet, bridging the receptor with gustducin. Together with a pocket-specific BRET-based ligand binding assay, these results illuminate bitter taste signaling and provide tools for a site-targeted compound design.
CRIS-Team Scopus Importer:2024-11-29

Discovery of 2-Aminopyrimidines as Potent Agonists for the Bitter Taste Receptor TAS2R14 - Waterloo, Lukas; Hübner, Harald; Fierro, Fabrizio; Pfeiffer, Tara; Brox, Regine; Löber, Stefan; Weikert, Dorothée; Niv, Masha Y.; Gmeiner, Peter (Journal of Medicinal Chemistry, 2023)
The bitter taste receptor TAS2R14 is a G protein-coupled receptor that is found on the tongue as well as in the human airway smooth muscle and other extraoral tissues. Because its activation causes bronchodilatation, TAS2R14 is a potential target for the treatment of asthma or chronic obstructive pulmonary disease. Structural variations of flufenamic acid, a nonsteroidal anti-inflammatory drug, led us to 2-aminopyridines showing considerable efficacy and potency in an IP1accumulation assay. In combination with an exchange of the carboxylic moiety by a tetrazole unit, a set of promising new TAS2R14 agonists was developed. The most potent ligand 28.1 (EC50 = 72 nM) revealed a six-fold higher potency than flufenamic acid and a maximum efficacy of 129%. Besides its unprecedented TAS2R14 activation, 28.1 revealed marked selectivity over a panel of 24 non-bitter taste human G protein-coupled receptors.
CRIS-Team Scopus Importer:2023-03-24

Inhibiting a promiscuous GPCR: iterative discovery of bitter taste receptor ligands - Fierro, Fabrizio; Peri, Lior; Hübner, Harald; Tabor-Schkade, Alina; Waterloo, Lukas; Löber, Stefan; Pfeiffer, Tara; Weikert, Dorothée; Dingjan, Tamir; Margulis, Eitan; Gmeiner, Peter; Niv, Masha Y. (Cellular and Molecular Life Sciences, 2023)
The human GPCR family comprises circa 800 members, activated by hundreds of thousands of compounds. Bitter taste receptors, TAS2Rs, constitute a large and distinct subfamily, expressed orally and extra-orally and involved in physiological and pathological conditions. TAS2R14 is the most promiscuous member, with over 150 agonists and 3 antagonists known prior to this study. Due to the scarcity of inhibitors and to the importance of chemical probes for exploring TAS2R14 functions, we aimed to discover new ligands for this receptor, with emphasis on antagonists. To cope with the lack of experimental structure of the receptor, we used a mixed experimental/computational methodology which iteratively improved the performance of the predicted structure. The increasing number of active compounds, obtained here through experimental screening of FDA-approved drug library, and through chemically synthesized flufenamic acid derivatives, enabled the refinement of the binding pocket, which in turn improved the structure-based virtual screening reliability. This mixed approach led to the identification of 10 new antagonists and 200 new agonists of TAS2R14, illustrating the untapped potential of rigorous medicinal chemistry for TAS2Rs. 9% of the 1800 pharmaceutical drugs here tested activate TAS2R14, nine of them at sub-micromolar concentrations. The iterative framework suggested residues involved in the activation process, is suitable for expanding bitter and bitter-masking chemical space, and is applicable to other promiscuous GPCRs lacking experimental structures.
CRIS-Team Scopus Importer:2023-04-21
Keywords: Bitterness inhibitors; GPCR; Structure-based drug design; TAS2R; Taste

Rational design of agonists for bitter taste receptor TAS2R14: from modeling to bench and back - Di Pizio, Antonella; Waterloo, Lukas; Brox, Regine; Löber, Stefan; Weikert, Dorothée; Behrens, Maik; Gmeiner, Peter; Niv, Masha Y. (Cellular and Molecular Life Sciences, 2020)
Human bitter taste receptors (TAS2Rs) are a subfamily of 25 G protein-coupled receptors that mediate bitter taste perception. TAS2R14 is the most broadly tuned bitter taste receptor, recognizing a range of chemically diverse agonists with micromolar-range potency. The receptor is expressed in several extra-oral tissues and is suggested to have physiological roles related to innate immune responses, male fertility, and cancer. Higher potency ligands are needed to investigate TAS2R14 function and to modulate it for future clinical applications. Here, a structure-based modeling approach is described for the design of TAS2R14 agonists beginning from flufenamic acid, an approved non-steroidal anti-inflammatory analgesic that activates TAS2R14 at sub-micromolar concentrations. Structure-based molecular modeling was integrated with experimental data to design new TAS2R14 agonists. Subsequent chemical synthesis and in vitro profiling resulted in new TAS2R14 agonists with improved potency compared to the lead. The integrated approach provides a validated and refined structural model of ligand–TAS2R14 interactions and a general framework for structure-based discovery in the absence of closely related experimental structures.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Bioisosteric replacement; Bitter taste receptor; Drug design; GPCRs; Structure-based modeling

The Bitter Taste Receptor TAS2R14 as a Drug Target - Waterloo, Lukas; Löber, Stefan; Gmeiner, Peter (Chimia, 2022)
G protein-coupled receptors (GPCRs) mediate most of our physiological responses to hormones, neurotransmitters, and environmental stimulants. Besides human senses like vision and olfaction, taste perception is mostly mediated by GPCRs. Hence, the bitter taste receptor family TAS2R comprises 25 distinct receptors and plays a key role in food acceptance and drug compliance. The TAS2R14 subtype is the most broadly tuned bitter taste receptor, recognizing a range of chemically highly diverse agonists. Besides other tissues, it is expressed in human airway smooth muscle and may represent a novel drug target for airway diseases. Several natural products as well as marketed drugs including flufenamic acid have been identified to activate TAS2R14, but higher potency ligands are needed to investigate the ligand-controlled physiological function and to facilitate the targeted modulate for potential future clinical applications. A combination of structure-based molecular modeling with chemical synthesis and in vitro profiling recently resulted in new flufenamic acid agonists with improved TAS2R14 potency and provided a validated and refined structural model of ligand–TAS2R14 interactions, which can be applied for future drug design projects.
CRIS-Team Scopus Importer:2022-10-14
Keywords: Bitter taste receptor; Drug discovery; Flufenamic acid; GPCRs